2008
DOI: 10.1016/j.cell.2008.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor E2-2 Is an Essential and Specific Regulator of Plasmacytoid Dendritic Cell Development

Abstract: Summary Plasmacytoid dendritic cells (PDC) represent a unique immune cell type specialized in type I interferon (IFN) secretion in response to viral nucleic acids. The molecular control of PDC lineage specification has been poorly understood. We report that basic helix-loop-helix transcription factor (E protein) E2-2/Tcf4 is preferentially expressed in murine and human PDC. Constitutive or inducible deletion of murine E2-2 blocked the development of PDC but not of other lineages, and abolished IFN response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
632
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 572 publications
(665 citation statements)
references
References 45 publications
32
632
1
Order By: Relevance
“…PDCs can differentiate into MDCs after stimulation and genome-wide analysis showed that the gene expression profile of PDCs is closer to MDCs than to other hematopoietic cells [7,8]. The development of both PDCs and MDCs depends on Fms-like kinase 3 ligand (Flt3L), but the E2-2 transcription factor is uniquely required for PDCs differentiation [9,10].…”
Section: Background On Pdcs: History and Functionmentioning
confidence: 99%
“…PDCs can differentiate into MDCs after stimulation and genome-wide analysis showed that the gene expression profile of PDCs is closer to MDCs than to other hematopoietic cells [7,8]. The development of both PDCs and MDCs depends on Fms-like kinase 3 ligand (Flt3L), but the E2-2 transcription factor is uniquely required for PDCs differentiation [9,10].…”
Section: Background On Pdcs: History and Functionmentioning
confidence: 99%
“…Human and mouse pDC share a number of common features, including a large specific gene expression program [33], a strict dependency for their differentiation on the transcription factors Spi-B [50] and E2-2 [51,52] and a functional specialization in innate antiviral defense through high-level production of IFN-a/b in response to TLR7 or TLR9 triggering [53]. Strikingly, apart from their plasmacytoid morphology, it has not been possible to define yet a core phenotype for mouse and human pDC.…”
Section: Toward a Unifying Classification Of DC Subsets Across Tissuementioning
confidence: 99%
“…Rather, these data suggest that the underlying cellular process defining the size of the pDC compartment may either result from more subtle variations in pDC proliferation or apoptosis not detectable in the context of the assays performed in this study or from more complex hematopoieticdependent factors, including but not limited to the presence of a key cytokine, cell-cell interaction with other hematopoietic cells, and/or the rate of hematopoietic differentiation of pDC. To that effect, a number of genes (Spib, Tcf4, Irf4, Irf8, and Flt3) have been shown to contribute to the hematopoietic differentiation of pDC (7,11,12,14,15). Of these genes, Spib and Flt3l (Flt3 ligand) are encoded on chromosome 7 between 51 and 53 Mb, comprised within the NOD.NZW-Chr7 congenic interval contributing to the size of the pDC compartment.…”
Section: Discussionmentioning
confidence: 99%
“…IFN regulatory factor (IRF)-8 also proved to be a key transcription factor in pDC differentiation and function, as Irf8-deficient mice presented with a much reduced proportion of pDC along with a deficiency in type I IFN production upon viral infection (13). More recent studies have proposed that the E2-2 transcription factor serves as a specific regulator of the pDC transcription profile, acting upstream of both Spi-B and IRF-8, and revealed its importance in the maintenance of the pDC fate (14,15). Therefore, the differentiation of pDC is dependent on the timely expression of specific transcription factors.…”
mentioning
confidence: 99%